SARS-CoV-2 spike protein as a bacterial lipopolysaccharide delivery system in an overzealous inflammatory cascade. (14th October 2022) - Samsudin, Firdaus; Raghuvamsi, Palur; Petruk, Ganna; Puthia, Manoj; Petrlova, Jitka; MacAry, Paul; Anand, Ganesh S; Bond, Peter J; Schmidtchen, Artur
ABSTRACT: Accumulating evidence indicates a potential role for bacterial lipopolysaccharide (LPS) in the overactivation of the immune response during SARS-CoV-2 infection. LPS is recognized by Toll-like receptor 4, mediating proinflammatory effects. We previously reported that LPS directly interacts with SARS-CoV-2 spike (S) protein and enhances proinflammatory activities. Using native gel electrophoresis and hydrogen–deuterium exchange mass spectrometry, we showed that LPS binds to multiple hydrophobic pockets spanning both the S1 and S2 subunits of the S protein. Molecular simulations validated by a microscale thermophoresis binding assay revealed that LPS binds to the S2 pocket with a lower affinity compared to S1, suggesting a role as an intermediate in LPS transfer. Congruently, nuclear factor-kappa B (NF-κB) activation in monocytic THP-1 cells is strongly boosted by S2. Using NF-κB reporter mice followed by bioimaging, a boosting effect was observed for both S1 and S2, with the former potentially facilitated by proteolysis. The Omicron S variant binds to LPS, but with reduced affinity and LPS boosting in vitro and in vivo . Taken together, the data provide a molecular mechanism by which S protein augments LPS-mediated hyperinflammation.